SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PROGRAM PELATIHAN KERJA BERDASARKAN KOMPETENSI DENGAN METODE SAW - Siti Maulidya Nabila; Nadila Putri Hermawan; Nabila Aprillia (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The Decision Support System (DSS) for selecting employee training programs based on competencies is a vital tool for organizations aiming to enhance the quality of their human resources. This research utilizes the Simple Additive Weighting (SAW) method, which is recognized for its ability to provide objective, mathematical evaluations in determining the best training programs. The criteria used include training relevance, duration, cost, and the quality of the training provider. Using the SAW approach, alternative training programs are evaluated based on weighted criteria values, resulting in effective and efficient recommendations. This system was implemented in a company, and the results demonstrated that the SAW-based DSS significantly improves accuracy and objectivity in decision-making processes related to employee training.